World Development Indicators 2012 - World Bank (Washington, DC, 2012)
World Development Indicators 2012 is a compilation of relevant, high-quality, and internationally comparable statistics about development and the quality of people's lives. Organized around six themes, world view, people, the environment, the economy, states and markets, and global links, it aims to put data into the hands of policy makers, development specialists, students, and the public. The full dataset used to produce World Development Indicators contains more than 1,000 indicators for 216 economies, with many time series extending back to 1960. And, as a major part of the World Bank's open data initiative, the data are freely available for use and reuse under an open license. A companion printed volume, the little data book 2012, presents a selection of indicators for each economy, and the biennial statistics for small states presents data for less-populated developing countries. Any assessment of the Millennium Development Goals must acknowledge that amid all the signs of progress, there are gaps. Some targets will not be reached in this decade or the next. Likewise the statistical record is still incomplete; Continuing progress will require renewed commitment and careful monitoring.